NHC‐Catalyzed Metathesis and Phosphorylation Reactions of Disulfides: Development and Mechanistic Insights. Issue 26 (7th April 2017) - Crocker, Reece D.; Hussein, Mohanad A.; Ho, Junming; Nguyen, Thanh V.
Abstract: The development of efficient methods for the metathesis and phosphorylation reactions of disulfide compounds is of widespread interest due to their important synthetic utility in polymer, biological, medicinal and agricultural chemistry. Herein, we demonstrate the use of N‐heterocyclic carbenes (NHCs) as versatile organocatalysts to promote these challenging reactions under mild conditions. This metal‐ and oxidant‐free protocol is operationally simple with very short reaction times. The interplay between the nucleophilicity and basicity of NHCs in these reactions were also elucidated by NMR studies and high‐level ab initio calculations. Abstract : In an instant ! N‐heterocyclic carbenes (NHCs) served as versatile organocatalysts to promote disulfide exchange and phosphite–disulfide coupling reactions under mild conditions. This metal‐ and oxidant‐free protocol is operationally simple and highly efficient with very short reaction times.